Attention Redirection Using Binaurally Spatialised Cues Delivered Over a Bone Conduction Headset. (September 2016) - Barde, Amit; Ward, Matt; Helton, William S.; Billinghurst, Mark; Lee, Gun
Visual search performance was studied using auditory cues delivered over a bone conduction headset. Two types of auditory cues were employed to evaluate the effectiveness of such cues in an attention redirection task. Participants were required to locate and shoot targets at one of four locations on a screen when one of the two audio cues was delivered. Reaction and target acquisition times were significantly reduced when the binaurally spatialised cues were used compared to unlocalisable, monophonic cues. This appears to suggest that an auditory cue with directional information is far superior at aiding search tasks or alerting the user to redirect attention in the real-world space in comparison to a centered 'monophonic' cue. The results demonstrate the effectiveness of a binaurally spatialised, dynamic cue and point to its potential use in an information rich environment to provide useful and actionable information.